Răspuns:
[tex] (3\sqrt{15} + 2 \sqrt{10} ) \times ( \sqrt{3} - \sqrt{2} ) = \\ 3 \sqrt{15 } \times \sqrt{3} - 3 \sqrt{15} \times \sqrt{2} + 2 \sqrt{10} \times \sqrt{3} - 2 \sqrt{10} \times \sqrt{2} = \\ 3 \sqrt{45} - 3 \sqrt{30} + 2 \sqrt{30} - 2 \sqrt{20} = \\ 3 \times ( \sqrt{45} - \sqrt{30} ) + 2 \times ( \sqrt{30} - \sqrt{20} ) = \\ 3 \times (3 \sqrt{5} - \sqrt{30} ) + 2 \times ( \sqrt{30} - 2 \sqrt{5} ) = \\ 9 \sqrt{5} - 3 \sqrt{30} + 2 \sqrt{30} - 4 \sqrt{5} = \\ 5 \sqrt{5} - \sqrt{30} [/tex]